Determining Parameters of Whistler Waves Trapped in High‐Density Ducts. Issue 12 (5th December 2021) - Williams, Daniel D.; Streltsov, Anatoly V.
Abstract: We investigate the possibility of identifying the perpendicular and parallel wavelengths (or wave numbers) of the very‐low‐frequency (VLF) whistler‐mode waves trapped inside the high‐density duct. This will be done by using information about the wave frequency, background magnetic field, and plasma density inside and outside of the duct. This data is collected from observations by the Van Allen Probes satellites. We developed a three‐step procedure based on the analysis of the whistler wave dispersion relation and numerical simulations of the electron‐magnetohydrodynamics model. We use this model to identify the parallel and perpendicular wave numbers of the "most trapped" wave. The first two steps of this procedure identify the ranges of the parallel and perpendicular wavelengths of the waves trapped inside the duct. The third step uses numerical simulations to determine the parameters of the "most trapped" wave from the aforementioned ranges. This procedure has been applied to the retrieved data from the Van Allen Probes in order to analyze the structure of VLF waves observed in the equatorial magnetosphere. Key Points: We develop a three‐step procedure to identify parallel and perpendicular wave numbers of the trapped waves We applied the developed procedure to identify parameters of the waves observed by RBSP‐B We study very‐low‐frequency waves observed by the RBSP‐B satellite in the high‐density ducts in the magnetosphere